Pathogenic Biofilm Removal Potential of Wild-Type Lacticaseibacillus rhamnosus Strains - Gregoria Mitropoulou; Vasiliki Kompoura; Grigorios Nelios; Yiannis Kourkoutas (Pathogens, 2023)
The emergence of antimicrobial resistance remains one of the greatest public health concerns. Biofilm formation has been postulated as a mechanism of microbial pathogens to resist antimicrobial agents. Lactic Acid Bacteria (LAB) and their metabolites have been proposed to combat bacterial biofilms due to their antimicrobial activity. In this vein, the aim of the present study was to investigate the biofilm removal potential of cell-free supernatants (CFSs) of five wild-type Lacticaseibacillus rhamnosus strains, isolated from Greek natural products, in comparison to the commercially available L. rhamnosus GG strain, against biofilms formed by common foodborne pathogens (Salmonella Enteritidis, Salmonella Typhimurium, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus). The biofilm removal activity of LAB was assessed on a two-day-old mature biofilm using a microtiter plate-based procedure. Both non-neutralized and neutralized CFSs removed biofilms in a concentration-dependent manner. The biofilm removal activity of the non-neutralized CFSs was significantly higher compared to the neutralized CFSs, as expected, with ranges of 60–89% and 30–80%, respectively. The biofilm removal efficiency of L. rhamnosus OLXAL-3 was significantly higher among the wild-type L. rhamnosus strains tested (20–100% v/v). In conclusion, our results suggest the great potential of the application of wild-type L. rhamnosus strain’ CFSs as effective natural agents against pathogenic bacterial biofilms.